Влияние наведенного потенциала секций высоковольтного делителя напряжения на его характеристики - Анохин, Ю.Л.; Атарод, С.; Бржезицкий, В.А.; Гаран, Я.А.; Маслюченко, И.Н. (Технічна електродинаміка, 2012)
The electric field pattern in a real construction of a high-voltage resistive-capacitive voltage divider is explored. Formulas and a procedure of the calculation of geometrical parametres of a circuit of a high-voltage arm of a voltage divider are received. Dependences of errors of scale transformation of a high voltage for dividers with the various constructions are result.